COVID-19 and Remote Learning: The Home and the School - Friesen, Norm (Philosophical Inquiry in Education)

(untitled) (Canadian Philosophy of Education Society, 2022)
One area that is almost certain to be of some concern in the coming wave of COVID-related publications is the question of home versus school as “learning environments” – as specifiable sets of conditions for facilitating and shaping the ongoing learning process. “Learning,” in turn, is conventionally understood as a neurological and cognitive process that occurs all the time, with institutional learning environments cultivating more formal and regulated learning, but hardly erasing its original, “natural” characteristics. Home and school, however, are much more than just different cognitive environments; they represent heterogeneous, even mutually exclusive social and cultural systems, spheres, or worlds. Each is characterized by its own roles, relations, habits, and experiences. Given that this article appears in a philosophical forum, it takes as its focus an original philosophical treatment of the question of the domestic and scholastic spheres: Hegel’s previously untranslated remarks from an 1811 graduation address to a school in Nuremberg. Besides introducing a “new” Hegel text to English-language readers, the overview that follows also sheds light on a particular way of contrasting school and family life.